2013
DOI: 10.1186/cc12861
|View full text |Cite
|
Sign up to set email alerts
|

Impact on survival of whole-body computed tomography before emergency bleeding control in patients with severe blunt trauma

Abstract: IntroductionWhole-body computed tomography (CT) has gained importance in the early diagnostic phase of trauma care. However, the diagnostic value of CT for seriously injured patients is not thoroughly clarified. This study assessed whether preoperative CT beneficially affected survival of patients with blunt trauma who required emergency bleeding control.MethodsThis retrospective study was conducted from January 2004 to December 2010 in two tertiary trauma centers in Japan. The primary inclusion criterion was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 19 publications
2
64
0
5
Order By: Relevance
“…Patients in the WBCT group had higher ISS than those in the control group in five studies [19]-[21],[40],[41]. On the contrary, in the study by Wada et al [23], patients in the NWBCT group had higher ISS than those in the WBCT group. In the study of Hutter et al [21], 831 patients were included after the introduction of a CT-scan policy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients in the WBCT group had higher ISS than those in the control group in five studies [19]-[21],[40],[41]. On the contrary, in the study by Wada et al [23], patients in the NWBCT group had higher ISS than those in the WBCT group. In the study of Hutter et al [21], 831 patients were included after the introduction of a CT-scan policy.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that the association between WBCT and lower mortality did not change and the pooled OR was 0.77 (95% CI: 0.63 to 0.94; P  = 0.009) with significant heterogeneity (I 2  = 69%). Similarly, a sensitivity analysis was performed after excluding the study by Wada et al [23], which revealed that WBCT was still significantly associated with lower mortality rate (OR, 0.72, 95% CI: 0.59 to 0.89; P  = 0.002) with significant heterogeneity (I 2  = 75%). Finally, a further sensitivity analysis was performed after simultaneously excluding these two studies.…”
Section: Resultsmentioning
confidence: 99%
“…Data from retrospective studies suggest that full body trauma CT scanning is associated with a reduction in missed injuries and overall mortality. 3,4,20 The REACT-2 study is currently examining this premise by determining whether immediate total-body CT scanning during the primary survey in trauma patients compared with conventional imaging supplemented with CT scanning reduces mortality. 12 Until the results of this study are published, whole-body CT scanning is likely to continue which means that radiation dose reduction strategies in critical care patients will have to focus on imaging undertaken after discharge from the ED.…”
Section: Discussionmentioning
confidence: 99%
“…2 The use of whole-body CT scans (from occiput to sacrum) in the early resuscitation period of trauma patients, has been shown to increase the probability of survival in some retrospective studies 3,4 but evidence of definitive improvements in clinical outcomes is lacking at the present time. 5 Causal links between ionising radiation and carcinogenesis became apparent from the lifespan study of Japanese atomic bombs survivors, with the most recent Biological Effects of Ionising Radiation report attributing a 1% risk of carcinogenesis from exposure to 100 mSv of ionising radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Por tanto, es esencial realizar un diagnóstico y detección precoz de dichas lesiones. A los métodos diagnósticos tradicionales, se han añadido otros, como la Focused Assessment Sonography in Trauma (ECO-FAST), la TAC helicoidal, la angiografía digital, etc., que facilitan, no solo la localización, sino la extensión y el alcance de las lesiones para una mejor aproximación quirúrgica 56 .…”
Section: Control De La Hemorragia: Cirugía De Control Del Dañounclassified